2018
DOI: 10.1126/scitranslmed.aat8806
|View full text |Cite
|
Sign up to set email alerts
|

A database of tissue-specific rhythmically expressed human genes has potential applications in circadian medicine

Abstract: The discovery that half of the mammalian protein-coding genome is regulated by the circadian clock has clear implications for medicine. Recent studies demonstrated that the circadian clock influences therapeutic outcomes in human heart disease and cancer. However, biological time is rarely given clinical consideration. A key barrier is the absence of information on tissue-specific molecular rhythms in the human body. We have applied the cyclic ordering by periodic structure (CYCLOPS) algorithm, designed to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
246
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(258 citation statements)
references
References 45 publications
12
246
0
Order By: Relevance
“…In addition, biological time strongly influences drug responses. Absorption, distribution, metabolism and excretion, along with efficacy, and/or toxicity of drugs, all have pronounced diurnal fluctuations (Levi & Schibler, ; Ruben et al, ). The effects in the PK of drugs result from rhythmic changes in absorption rates, drug‐protein binding, pH, membrane viscosity, levels of liver enzymes, transport proteins and ion channels, peripheral, liver, and renal blood flow, GFR and urine flow, and pH, which influences the degree of urine acidification (Dallmann, Okyar, & Lévi, ; Levi & Schibler, ).…”
Section: Impact Of Circadian Rhythms On Pharmacological Studiesmentioning
confidence: 99%
“…In addition, biological time strongly influences drug responses. Absorption, distribution, metabolism and excretion, along with efficacy, and/or toxicity of drugs, all have pronounced diurnal fluctuations (Levi & Schibler, ; Ruben et al, ). The effects in the PK of drugs result from rhythmic changes in absorption rates, drug‐protein binding, pH, membrane viscosity, levels of liver enzymes, transport proteins and ion channels, peripheral, liver, and renal blood flow, GFR and urine flow, and pH, which influences the degree of urine acidification (Dallmann, Okyar, & Lévi, ; Levi & Schibler, ).…”
Section: Impact Of Circadian Rhythms On Pharmacological Studiesmentioning
confidence: 99%
“…Recent studies have suggested that the expression levels of up to 43% and 50% of mouse and human genes, respectively, across different tissues are regulated by the circadian clock mechanism mostly in a tissue‐specific manner . Consequently, biological processes such as cell cycle, DNA repair, blood pressure, heart rate, platelet aggregation, thrombus formation, and sleep‐wake cycle are regulated by the circadian clock to maintain heart homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies have suggested that the expression levels of up to 43% and 50% of mouse and human genes, respectively, across different tissues are regulated by the circadian clock mechanism mostly in a tissue-specific manner. 12,13 Consequently, biological processes such as cell cycle, DNA repair, blood pressure, heart rate, platelet aggregation, thrombus formation, and sleep-wake cycle are regulated by the circadian clock to maintain heart homeostasis. [14][15][16] Nevertheless, circadian rhythms are disrupted with modern living conditions such as chronic jetlag or shift work (conditions characterized by repeated misalignment of the internal clock to the external light/dark cycle), which subsequently desynchronize the expression of CCGs in the body, giving rise to deleterious cellular and systemic effects on health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Following pioneering bunker experiments conducted by Juergen Aschoff, 175 a number of powerful approaches for in vivo human clock studies have been developed. 81 This methodology holds great promise for minimizing the need of tissue sampling, thus rendering the sample collection significantly less invasive. However, these studies are highly demanding for the participating volunteers, due to their long duration and protocol complexity, and are thus of limited usage, particularly in the context of human pathologies.…”
Section: Dissecting the Human Clock In A Petri Dish: Molecular Insimentioning
confidence: 99%
“…Those protocols are based on "constant routine" which imposes constant light, temperature, posture, evenly distributed food intake and usually sleep deprivation for the duration of 24 hours or more, and "forced desynchrony", discussed in the previous chapter. 81,176 Considerably less invasive methods for studying human clocks in vivo comprise questionnaires, notably the Munich Chronotype Questionnaire, 177,178 along with simple measurements that can be conducted in the home environment of the participant, such as activity rhythm by actigraphy, 179 thoracic skin temperature measurement using contact thermometry, 180 or serial urine and saliva sampling followed by melatonin assessment. Additionally, a lack of protocol standardization limits the direct comparison of the outcomes between the different studies.…”
Section: Dissecting the Human Clock In A Petri Dish: Molecular Insimentioning
confidence: 99%